2015
DOI: 10.1155/2015/273151
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Discectomy via Transforaminal Route for Discal Cyst

Abstract: Background. Discal cyst has been identified as a rare cause of low back pain and radiating leg pain. The pathogenesis and management of this condition are still debated. The largest number of reported cases had undergone microsurgery while very few cases have been treated with percutaneous endoscopic discectomy (PED). Methods. An 18-year-old boy complained of low back pain radiating to right leg after a minor road traffic accident. Diagnosis of a discal cyst at L4-L5 level was made based on magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
(29 reference statements)
0
13
0
5
Order By: Relevance
“…However, it is reported that there is still the possibility of recurrence after CT-guided puncture and aspiration Discal Cyst of the Lumbar Spine J Med Cases. 2020;11(6):178-181 [3,12]. Therefore, we prefer to perform radical resection of discal cysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is reported that there is still the possibility of recurrence after CT-guided puncture and aspiration Discal Cyst of the Lumbar Spine J Med Cases. 2020;11(6):178-181 [3,12]. Therefore, we prefer to perform radical resection of discal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…has not yet been established [2][3][4]. Percutaneous endoscopic lumbar discectomy (PELD) is a minimally invasive surgical technique, especially to preserve paraspinal structures and avoid back muscle damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most discal cysts are managed by partial hemi laminectomy and microscopic resection of the cyst under general anesthesia. CT-guided aspiration is another minimally invasive option, but it is associated with a high recurrence rate and requires radical excision of the intraspinal cyst 6,10,19) .…”
Section: Macnabs: Outcome Assesment Of Patients Satisfactionmentioning
confidence: 99%
“…Other reports have completed resection by percutaneous endoscopic surgery, but the recurrence rate with percutaneous C-arm guide aspiration is not yet known. Recurrence has been reported by Lee et al and Kang et al after surgical removal of a discal cyst, but no studies have assessed recurrence after treatment with the 1,414-nm Nd:YAG laser 1,5,6,[9][10][11]17,19,20) .…”
Section: Macnabs: Outcome Assesment Of Patients Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation